Theoretical issues and design of laser systems (LS) - Kazbekova, Sevda; Казбекова, Севда Агаммад (Запоріжжя : Видавничий дім «Гельветика», 2026)
EN: During the last decade, significant achievements in quantum electronics have made it possible not only to create unique ranging systems based on lasers but also to effectively apply them in various fields of science and technology. In particular, laser ranging systems enable reliable observation of the motion of objects with different target purposes. It is well known that any ranging system is intended to obtain information about a remote object. This information is delivered by a ranging signal and extracted through special signal-processing techniques. The main feature of lidar systems is that the received signal is not generated by the observed object specifically to transmit information. Instead, it represents either the object’s own radiation or the result of reflection of probing radiation from the surface of the object. Depending on the type of ranging radiation used, different types of information about the object can be obtained. The efficiency of a ranging system is determined, on the one hand, by the amount of information received as well as the speed and accuracy with which this information is obtained, and on the other hand, by how technically feasible it is to implement such a system. From these perspectives, laser ranging systems have increasingly been preferred in recent years. These systems allow high-precision measurement of the coordinates and velocity of objects, provide information about their shape, and determine the characteristics of their surfaces. At the same time, laser ranging systems can have relatively compact dimensions and are energetically efficient. This advantage is largely due to the fact that their probing signal can be concentrated within a narrow beam angle, which is often comparable to the angular region in which the observed object is visible. /// UA: Протягом останнього десятиліття значні досягнення в галузі квантової електроніки дали змогу не лише створювати унікальні далекомірні системи на основі лазерів, але й ефективно застосовувати їх у різних сферах науки і техніки. Зокрема, лазерні далекомірні системи забезпечують надійне спостереження за рухом об’єктів різного призначення. Відомо, що будь-яка далекомірна система призначена для отримання інформації про віддалений об’єкт. Ця інформація передається за допомогою зондувального сигналу та вилучається за допомогою спеціальних методів обробки сигналів. Основною особливістю лідарних систем є те, що прийнятий сигнал не генерується спостережуваним об’єктом спеціально для передавання інформації. Натомість він являє собою або власне випромінювання об’єкта, або результат відбиття зондувального випромінювання від його поверхні. Залежно від типу використовуваного зондувального випромінювання можна отримати різні види інформації про об’єкт. Ефективність далекомірної системи визначається, з одного боку, обсягом отриманої інформації, а також швидкістю й точністю її отримання, а з іншого – технічною можливістю реалізації такої системи. З огляду на ці аспекти, останніми роками все більшого поширення набувають лазерні далекомірні системи. Вони забезпечують високоточне вимірювання координат і швидкості об’єктів, надають інформацію про їхню форму та дозволяють визначати характеристики їхніх поверхонь. Водночас лазерні далекомірні системи можуть мати відносно компактні розміри та є енергетично ефективними. Ця перевага значною мірою зумовлена тим, що їхній зондувальний сигнал може бути зосереджений у вузькому куті променя, який часто є співмірним із кутовою областю, в якій спостерігається об’єкт.
Теоретичні питання та проєктування лазерних систем (LS)
Keywords: laser ranging systems; lidar; signal processing; receiver systems; optical design; measurement accuracy; лазерні далекомірні системи; лідар; обробка сигналів; приймальні системи; оптичне про- єктування; точність вимірювань